Measuring the self-generated magnetic field and the velocity of plasma flow in a pulsed plasma accelerator - Tazhen, A.; Dosbolayev, M.K. (Recent Contributions to Physics, 2021)
In phase of radial compression the unsteady plasma flow at the exit of a pulsed plasma accelerators is related to the generation of fast high-energy charged particle beams, to plasma density perturbations, to the internal plasma pressure is opposite to the external magnetic pressure (B2/2μ0) associated with plasma column’s self-generated magnetic field. The last one listed above is of particular interest. The investigation of the magnetic field of plasma flow relatively gives information about the above mutually close factors cause to plasma flow instability.In this paper a miniature high-frequency magnetic probe are made for measuring and further investigating the pulsed self-generated magnetic field of plasma flow, in particular, at the exit of the accelerator in an experimental setup of PPA (located in KazNU, IETP). The magnetic probe dimensions are following: coil diameter is 2,12 mm, number of turns is 7, copper wire diameter is 150 μm, and winding length is 1, 1 mm. The coil inductance is about 0,113 μH and the temporal resolution of the magnetic probe is 2,3 ns. The magnetic probe was calibrated using a Hall sensor on the magnetic field of a multi-layered solenoid connected to an alternating power source of 15 A. Thus, the evaluated measurement error of the probe was no more than 10%.
Keywords: pulsed plasma accelerator; plasma flow; self-generated magnetic field of plasma flow; magnetic probe